2020
DOI: 10.1186/s13287-020-01879-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy assessment of mesenchymal stem cell transplantation for burn wounds in animals: a systematic review

Abstract: Background: Clinically, severe burns remain one of the most challenging issues, but an ideal treatment is yet absent. Our purpose is to compare the efficacy of stem cell therapy in a preclinical model of burn wound healing. Methods: Research reports on mesenchymal stem cells (MSCs) for burn wound healing were retrieved from 5 databases: PubMed, Embase, MEDLINE, Web of Science, and the Cochrane Library. The primary outcomes reported in this article include the un-healing rate of the wound area, the closure rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 62 publications
2
4
0
2
Order By: Relevance
“…Stem cells act through multiple mechanisms and improve the efficacy of stem cell therapy [ 18 20 ]. In addition to the direct transformative and regenerative abilities of transplanted cells, the regulation of immune cells by stem cells plays a key role in tissue regeneration [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stem cells act through multiple mechanisms and improve the efficacy of stem cell therapy [ 18 20 ]. In addition to the direct transformative and regenerative abilities of transplanted cells, the regulation of immune cells by stem cells plays a key role in tissue regeneration [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Berdasarkan data WHO, kasus mortalitas akibat luka bakar diperkirakan sekitar 265.000 jiwa setiap tahunnya. 2 Dari studi epidemiologi di Rumah Sakit Cipto Mangunkusumo (RSCM) tahun 2011-2012 data pasien yang dirawat selama periode 2 tahun adalah 303 pasien dengan sebagian besar pasien dengan luka bakar berat sebanyak 45,87%. Sedangkan data dari RSUP Sanglah Denpasar tahun 2012 dari total 154 pasien yang dirawat, sebanyak 13 orang meninggal (8,42%) akibat ledakan api dengan luka bakar luas dan dalam.…”
Section: Latar Belakangunclassified
“…Selain itu timbulnya jaringan parut dan kontraktur juga akan mempengaruhi fungsi pasien seperti terbatasnya ruang gerak sendi. 2,4 Oleh karena itu dibutuhkan suatu inovasi dalam penatalaksanaan kasus luka bakar untuk menghasilkan waktu penyembuhan yang lebih cepat dan luaran klinis yang lebih memuaskan. Metode yang sedang diteliti saat ini adalah penggunaan sel punca atau stem cell.…”
Section: Latar Belakangunclassified
“…MSCs are pluripotent cells with extensive self-renewal potential and can differentiate into various non-hematopoietic cells (osteoblast, chondrocyte, myocyte, adipocyte, hepatocyte, fibroblasts, enterocyte, neurocyte, endothelium, tendon, and ligament) under certain conditions [5]. In recent years, a growing body of research has reported MSCs can contribute to healing of injured tissues and curing many diseases [6][7][8][9][10] by inhibition of apoptosis, inflammation, and fibrosis, promotion of angiogenesis, release of repair factors, and immunomodulation [11,12].…”
Section: Introductionmentioning
confidence: 99%